1988
DOI: 10.7773/cm.v14i4.618
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Insecticides In Fishes From The Mexicali Valley, Baja California, Mexico

Abstract: RESUMEN Este estudio describe insecticidas organoclorados en peces Cyptinus cnrpio y Tihpia sp. colectados durante 1985-86 en las aguas de los canales y drenes del valle agrfcola de Mexicali, situado en Baja California, México. Las concentracionesde DDTfueron significativas en todas las muestras colectadas. No se detectaron niveles importantes de otros compuestos orgánicos sint6ticos. De las dos especies de peces examinadas, C. carpio mostró concentraciones mayores de DDT. Se discuten los resultados en relació… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
1
1
2
Order By: Relevance
“…Some authors (e.g., Gómara et al 2005) report PCDD/F concentrations on a wet weight basis to avoid seasonal variations of the fat content of fish species, which can vary considerably over one year due to different maturation states. On the other hand, Wu et al (2001) argued that valid comparisons between different species are possible only if the concentrations are normalized by lipid content; however, pollutant concentration and lipid content are not always correlated (Gutiérrez-Galindo et al 1988, Amado et al 2006. In this study, PCDD/F concentrations in fish from Ensenada, Carmen City and Patzcuaro Lake did correlate with lipid content but fish from El Barril did not.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Some authors (e.g., Gómara et al 2005) report PCDD/F concentrations on a wet weight basis to avoid seasonal variations of the fat content of fish species, which can vary considerably over one year due to different maturation states. On the other hand, Wu et al (2001) argued that valid comparisons between different species are possible only if the concentrations are normalized by lipid content; however, pollutant concentration and lipid content are not always correlated (Gutiérrez-Galindo et al 1988, Amado et al 2006. In this study, PCDD/F concentrations in fish from Ensenada, Carmen City and Patzcuaro Lake did correlate with lipid content but fish from El Barril did not.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies on other organochlorine compounds in fish have shown that residue concentrations vary markedly with age (and therefore with size and weight), generally bioaccumulating through life (Antunes et al 2001, Jacobs et al 2002, Vives et al 2005. On the other hand, Gutiérrez-Galindo et al (1988) did not find this correlation. Although variations of organochlorine pesticides and polychlorinated biphenyls (PCBs) in relation to the reproductive cycle of some organisms have been documented (Gutiérrez-Galindo et al 1984, Hummel et al 1989, Femeira and Vale 2001, this relation has not been established for PCDDs/Fs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations